Basic education and research in the classroom - doi: 10.4025/actascieduc.v35i2.20649 - Nilda Stecanela; Guillermo Williamson (Universidade Estadual de Maringá, 2013)
Relationships between the challenges of Basic Education, especially those related to contemporary school, and the research-linked educational challenges are investigated, based on theoretical reflections on the employment of research in the classroom as an educational principle. The arguments are foregrounded on the analysis of aspects associated to the genesis of education and school crises. Current paper focuses on the importance of the teachers' reflective practice and on their constitution as researchers-teachers for the implementation of the language game provided by classroom research, taking into consideration Freire's dialogue. It underlines the active teaching methodologies that try to bridge the communication gap between school cultures and children's and young people's cultures, linked to everyday life dilemmas and with experience-built knowledge.